TINJAUAN YURIDIS RENCANA PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA NUKLIR DI INDONESIA BERDASARKAN NUCLEAR SAFETY CONVENTION TAHUN 1994 DIKAITKAN DENGAN ASAS PEMBANGUNAN BERKELANJUTAN - M. Sobirin Hafiz Ar-Rizqi; Zulfikar Jayakusuma; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Utilization of Nuclear Energy is inseparable from a strict regulation and variousstandards that must be met and must pay attention to various environmental impacts that mayoccur. The purpose of writing this thesis is to determine the Implementation of Nuclear SafetyConvent ion 1994 in Indonesia is associated with the development plan of a Nuclear PowerPlant, as well as knowing whether the plan for the Development of a Nuclear Power Plant inIndonesia supports Sustainable DevelopmentThe type of conducted research is normative-juridical research by examining problems interms of applicable principles of international law, by first identifying the legal principles thathave been formulated in the source international law. In this study, the data sources used weresecondary data with primary, secondary, and tertiary legal materials that carried out by means oflibrary research.From the results of the study, it was found that the development of nuclear energyregulation confirms the existence of legal protection in general which is regulated in previouslegal provisions and regulates legal protection specifically at this time. And the environmentalimpacts that may arise from the use of nuclear power can be very dangerous and threaten thesafety of human life. If the nuclear power is used as a nuclear reactor or nuclear weapon, then inthe event of a leak or accident it will cause radiation and environmental damage which hasdirect and indirect effects on humans and the environment, and the effects of radiation can onlybe seen after decades. after the accident..Keywords: Nuclear Energy - Environmental Law- Sustainable Development